Smart city: A model for African realities - (:unkn) unknown (My University, 2024)
Smart cities are urban policies that use communication and information technologies (ITCs) to accelerate a city’s ecological transition and boost its international competitiveness. In a context of the African cities, influenced by complex cultures, fast growing papulation, potential changes in local governance and weak economies, the implementation of Smart city would transform the face of urban centres and African capitals. Define Smart city model with an Africanised posture and consider its implementation will require a study of the relationship between the urban or rural digital network to the other networks in the city, the participation all the actors of decentralization in this new form of local development and of the necessary funding. In other to accelerate the ecological transition of the African cities, the integration of Smart cities into public policies becomes a priority for Decentralized Local Authorities (DLAs) which have the responsibility of modernize their cities. To achieve this, it is imperative to integrate the cultural, environmental and even behavioural habits of local populations into the contents linked to the digital transformation Black Africa Cities. This integration is not involved only in the activities of the African cities but also in the economic model of the African companies like in their international actions. As part of this debate, the aim will be to present what the future smart city of Black Africa should look like, solving multi-sectorial problems. It will also propose an inclusive approach that makes of the cultural, economic and geographical specificities of each territory
Keywords: African Research